2007
DOI: 10.1177/1358863x07083363
|View full text |Cite
|
Sign up to set email alerts
|

Contrast-enhanced ultrasound imaging of atherosclerotic carotid plaque neovascularization: a new surrogate marker of atherosclerosis?

Abstract: An atherosclerotic plaque requires a nutrient blood supply, which is predominantly derived from arterial vasa vasorum. A variety of factors (environmental and genetic) contribute to the initiation and growth of atherosclerosis within vessel walls. Chemotactic factors, such as tissue ischemic and hypoxic factors, stimulate the release of vascular endothelial growth factor (VEGF) proteins, resulting in vessel wall angiogenesis. These developments often precede the formation of the luminal plaque. In this report,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
168
1
9

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 221 publications
(181 citation statements)
references
References 19 publications
3
168
1
9
Order By: Relevance
“…Contrast-Enhanced Ultrasound CEUS represents a simple and noninvasive technique for the evaluation of plaque vascularization, allowing for the detection of plaque vasa vasorum that are abundant in vulnerable plaques [86][87][88].…”
Section: Contrast Enhancement (Us-mri-ct)mentioning
confidence: 99%
“…Contrast-Enhanced Ultrasound CEUS represents a simple and noninvasive technique for the evaluation of plaque vascularization, allowing for the detection of plaque vasa vasorum that are abundant in vulnerable plaques [86][87][88].…”
Section: Contrast Enhancement (Us-mri-ct)mentioning
confidence: 99%
“…Such plaques are prone to rupture due to increased lipid content, macrophage density and intraplaque hemorrhage. Homogeneous echo plaques are also associated with an increased risk of ischemic stroke (12,35). Standard ultrasonography of the patients in the current study at baseline revealed either uniform or predominant echolucent lesions.…”
Section: Discussionmentioning
confidence: 51%
“…This has led to increasing interest in the inflammatory and histological processes that occur in atherosclerotic lesions and give rise to cerebrovascular events (34,35). A noninvasive method capable of evaluating plaque neovascularization is required to evaluate these processes.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, all the studies which use contrast-enhanced ultrasound for the detection and quantification of vasa vasorum employ visualbased semi-quantitative approaches [44 -46]. Shah et al used a semi-quantitative grading scale (grade 0 = no neovascularization, grade 1 = limited neovascularization, grade 2 = moderate neovascularization, grade 3 = pulsating, arterial vessel) to provide a distinction between the variations observed in intraplaque neovascularization [44]. Using a similar, dichotomous grading system, various recent studies categorized contrast-enhanced ultrasound enhancement as no contrast effect (grade 1) or high (grade 2) based on the visual detection of the contrast effect within the plaque [46].…”
Section: Plaque Neovascularization On Contrast-enhanced Ultrasound Immentioning
confidence: 99%
“…Using a similar, dichotomous grading system, various recent studies categorized contrast-enhanced ultrasound enhancement as no contrast effect (grade 1) or high (grade 2) based on the visual detection of the contrast effect within the plaque [46]. Systematic histopathological validation revealed a direct positive correlation between contrast enhancement using this semi-quantitative grading scale and histology [44,45]. Furthermore, wholly consistent with the concept that more vulner- able plaque contains a higher degree of neovascularization, recent retrospective studies revealed the association between plaque enhancement on contrast-enhanced ultrasound imaging and clinical symptoms including cerebrovascular events in patients with carotid atherosclerosis [19,46,47].…”
Section: Plaque Neovascularization On Contrast-enhanced Ultrasound Immentioning
confidence: 99%